Effects of Fe self-ion irradiation on a low carbon MX-ODS steel at 550°C - Xu, Yuwen; Yun, Di; Yan, Xu; Zhang, Ping; Yan, Wei; Li, Yanfen; Li, Chao; Li, Jiao; Zhang, Tongmin; Li, Jun; Zhou, Junjun; Kang, Long; et al. (Frontiers in Energy Research, 2023)
Oxide Dispersion Strengthened (ODS) steels with nano-scale oxides have become one of the candidate materials used in advanced nuclear reactor systems. A novel MX-ODS steel with extremely low carbon content was irradiated with 3 MeV Fe ions at 550°C up to peak damage of 70 dpa. The steel contains uniformly distributed Y2O3 nano-precipitates with an average size of 3.5 nm and a number density of 5 × 1022/m3. A V-rich shell was found surrounding the core of Y, O, and Si at some particles. Two types of large precipitates, Y-Ta-Si oxides, and VN, were observed in the steel instead of carbides. Voids of very small size are present due to irradiation and the calculated void swelling was only 0.004%, suggesting good irradiation tolerance of the MX-ODS steel in this study. Fine and dense oxide nano-precipitates and their shell-core structure remained stable while the shape of large precipitates changed after irradiation.